Manufacturing Performance in Green Supply Chain Management - Wan Hasrulnizzam , Wan Mahmood; Ab Rahman, Mohd Nizam; Md Deros, Baba; Jusoff, Kamaruzzaman; Adi, Saptari; Zuhriah, Ebrahim; Abu Bakar, Mohd Hadzley; Sivarao, Subramonian; Jano, Zanariah (IDOSI Publications, 2013)
The purpose of the study is to examine the influence of manufacturing performance on green supply chain management amongst Malaysian companies. A conceptual model is proposed and is subjected to an empirical verification with the use of a survey of manufacturing companies in Malaysia. The AMOS structural equation modelling was used to measure the respondents’ overall perceptions of the green supply chain management and current manufacturing performance. Results indicate that improving manufacturing performance leads to an integrated green supply chain, which ultimately leads to an enhancement of environmental compliance as well as an optimisation of the operational resources and product recycling activities. However, most practices have a very weak correlation with overall manufacturing system performance. Being the first ever empirical investigation of the link between manufacturing performance and green supply chain management practices amongst organisations in Malaysia, this study helps industrialist to enhance improvement in productivity. Future research should include different industrial sectors or countries, to enable comparative studies. A larger sample would also allow a detailed cross-sector comparison.